Innovation Analysis of Case Tracking Information Technology (SIPP) of the Tulungagung Class IA Religious Court - puryanti, puryanti (Jurnal El-Pustaka, 2023)
The Tulungagung Religious Court is an institution that provides public services for those who wish to obtain justice in the field of cases. The role of information technology for the Religious Courts, especially in the administrative field, has a big influence on employees and companies so many jobs will be easier to do with information technology. The information technology referred to within the Religious Courts is the Case Tracing Information System (SIPP). The purpose of this study is to find out the innovation of the Case Tracing Information System (SIPP). In the Tulungagung Religious Court and the obstacles experienced in the implementation of the SIPP. The method used in this study is a qualitative research method using a descriptive approach. Meanwhile, the data collection method refers to journals and legislation regarding innovative case-tracking information systems at the Religious Court. Collecting data using observation techniques, and in-depth interviews to obtain valid and relevant data. Based on the innovation of the case tracking information system, is very influential in the main tasks of employees in managing case administration to improve public services. There are 6 informants in this study, namely leaders, judges, clerks, admins, and case parties.